Implications of role play on speaking performance and confidence in sixth grade EFL students (2022)
This study examines the implications of role-play on speaking performance and confidence in sixth grade EFL students. To achieve this, a research was conducted on 43 sixth grade students attending the educational institution Madre Laura in Cartagena, Colombia. During this process, a role-play activity was carried out and students were asked to submit a voluntary questionnaire about their perceptions of role-play and its implications for the speaking performance and confidence in English. The results of the study showed that role-play helped students improve their pronunciation, fluency and confidence in English.